Beban Kerja Guru Sekolah Dasar pada Masa Pandemi - Nurshavira, Adhe Aprilia; Wahyuningsih, Anik Setyo (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: The Covid-19 pandemic has had various impacts on life, from the economy, security, health, and education. The consequence that happened in the education field was the transformation of the learning system, it transformed into a distance learning system or online learning system. The system changed the workload of how the materials were given by the teacher either. Preliminary research was conducted in two primary schools namely SDN Petompon 02 and SD Labschool UNNES. Teachers' mental workload ranged between high and very high categories. Therefore, the research accomplishment will discover an idea about the workload of a primary school teacher caused by the Covid-19 outbreak. Methods: This research applied qualitative descriptive research and used a purposive sampling technique with the number of informants amounted to 30 teachers. Results: The results showed that there were differences in the workload of teaching hours between SDN Petompon 02 and SD Labschool UNNES which implemented an emergency curriculum. The mental workload of SDN Petompon 02 teachers was in the medium to very high category, meanwhile, the mental workload of SD Labschool UNNES teachers was in the high and very high category. This high mental workload is caused by the difficulty of teachers making adjustments to online learning methods, which mostly use technology. Conclusion: Suggestions for teachers are to are using the respite wisely and providing the time limits related to parental communication in clear. Suggestions for the headmasters as expected are effectuating the IT use training and providing counseling services for the teachers.